Raven tales. Musicians of the Sun [videorecording (DVD)] - Adams, Evan; Moore, Carmen; Evans Old Yellow Women (Indigenous Collection., 2017)
Snow has trapped the people inside, so Frog tells the story of when the Great Spirit sent Raven to free the Musicians of the Sun to bring light and music into the world.